Resection and Reconstruction of Robotic Hepatopancreatobiliary Surgery - LIU Rong; LIU Qu (Xiehe Yixue Zazhi, 2023)
Robotic system has overcome the limitations of traditional laparoscopy and promoted the development of minimally invasive surgery. However, in the early stage of robotic hepatopancreatobiliary surgery, the lack of resection and reconstruction technology compatible with the robotic system restricts its application. Based on the previous experience, we propose the circumvascular resection technique, which takes the main blood vessels as the mark, mobilizes the blood vessels and excises the soft tissues around the blood vessels, and the double-low reconstruction technique, which can improve the reconstruction quality by reducing the tissue tension and the tensile stress per unit area during the reconstruction. These two techniques can address the limitations of the robotic system including limit operating space and lack of force feedback, and help to improve surgical safety, reduce learning curve and promote the clinical application of robotic hepatopancreatobiliary surgery.